Environmental factors modulated the fatty acid profile of the shrimp Xiphopenaeus spp. in Cananéia and Ubatuba southeast Brazilian coast - Gonçalves, Geslaine Rafaela Lemos [UNESP] (2023)
Environmental characteristics influence the fatty acids (FAs) of aquatic organisms. Environmental factors and anthropic actions such as water pollution can impact FA composition. This directly affects the trophic network, especially when low-quality FA is provided to other trophic levels. The omnivore Penaeoidea shrimp is rich in proteins and polyunsaturated fatty acids (PUFA), representing an important node in the trophic web. We compared the FA composition of the commercially exploited seabob shrimp Xiphopenaeus spp. in two distinct coastal sites, Cananéia and Ubatuba, on the southeast Brazilian coast. Cananéia has a low human population density and is a preserved area with nearby mangroves, while Ubatuba is highly urbanised and influenced by tourism (increasing the domestic sewage), with diverse microhabitats but without mangrove influence. We found a total of 29 different FAs in seabob shrimp samples. Saturated FAs and PUFAS were the most representatives. For sex or age (juvenile and adult), deviations were found in the monosaturated FA, ω6, and ω3/ω6. However, FA composition was significantly different between sites, with Ubatuba presenting a lower abundance of FAs than Cananéia. The fatty acid composition of Xiphopenaeus spp. was influenced by environmental quality factors such as dissolved oxygen, chlorophyll, organic matter, and size gradient. The presence of high amounts of organic matter (especially sewage) during decomposition can decrease dissolved oxygen levels, reducing the quality of the first producers and limiting the availability of FAs for other trophic levels. The study suggests that water pollution and mangrove forests can impact the FAs of Xiphopenaeus spp., potentially reducing their nutritional value and causing an imbalance in the transference of FAs.